Spinsterhood Reasons and treatments (Journal of the College of Education for Women, 2018)
The research includes an introduction on Unmarried as one of the most dangerous phenomena's in Arab society in general and Iraqi society in specific especially after last decades wars that ruined the country and enlarged the number of unmarried women. First chapter dealt with the research problem that was increasing day after another while the percentage of unmarried women became 85% due to embargo and wars made by ex-regime that led to kill many Iraqis and decreasing marriage chances.The research aims to recognize the reasons behind that and tries to find solutions by using quest ways and tools to get rid of old habits that represent obstacle marriage. The research dealt with unmarried in Arab countries where National Institution statics were doleful. Then the research looked at the unmarried in Iraq as far as dealing with marriage as a social arrangement regulates the relationship between man and women in accordance with the culture of the society in making a family.